Kinetic Monte Carlo simulations of organic ferroelectrics - Cornelissen, Tim D.; Biler, Michal; Urbanavičiūtė, Indrė; Norman, Patrick; Linares, Mathieu; Kemerink, Martijn (Physical chemistry, chemical physics, 2019)
Ferroelectrics find broad applications, e.g. in non-volatile memories, but the switching kinetics in real, disordered, materials is still incompletely understood. Here, we develop an electrostatic model to study ferroelectric switching using 3D Monte Carlo simulations. We apply this model to the prototypical small molecular ferroelectric trialkylbenzene-1,3,5-tricarboxamide (BTA) and find good agreement between the Monte Carlo simulations, experiments, and molecular dynamics studies. Since the model lacks any explicit steric effects, we conclude that these are of minor importance. While the material is shown to have a frustrated antiferroelectric ground state, it behaves as a normal ferroelectric under practical conditions due to the large energy barrier for switching that prevents the material from reaching its ground state after poling. We find that field-driven polarization reversal and spontaneous depolarization have orders of magnitude different switching kinetics. For the former, which determines the coercive field and is relevant for data writing, nucleation occurs at the electrodes, whereas for the latter, which governs data retention, nucleation occurs at disorder-induced defects. As a result, by reducing the disorder in the system, the polarization retention time can be increased dramatically while the coercive field remains unchanged.